Acute Myeloid Leukemia - Wahyuni Wahyuni; Afifah Izzatul Zahra (STIKes Ibnu Sina Ajibarang, 2024)
Acute Myeloid Leukemia is part of a group of clinical diseases caused by genetic changes in stem cells in the bone marrow. This mutation causes the bone marrow to produce immature blood cells. Some patients with Acute Myeloid Leukemia (AML) often experience relapses in their illness. About 5% of patients have recurrences within 5 years in the extramedullary and about 29% have repeated in the bone marrow. Therapy in AML aims to achieve complete reduction and avoid duplication through chemotherapy and bone marrow transplantation. Bone marrow transplant is given to patients with acute myeloid leukemia with high cytogenetic risk. A complete remission rate of 80% can be achieved, especially in younger patients with overall 5-year survival of 40%. The data obtained came from primary data through history taking, physical examination, and supporting examinations. The results showed that the patient's complaints were related to the weakness that had been felt about 1 week ago. The weakness that is felt is getting heavier day by day. Laboratory examinations showed decreased levels of hemoglobin, platelets, and increased leukocytes. The management of this patient was carried out using non-pharmacological and pharmacological management by giving transfusions of PRC 3 bags and TC 10 bags and other supportive therapy during the treatment.